2019
DOI: 10.3390/molecules24213982
|View full text |Cite
|
Sign up to set email alerts
|

The Polyphenols as Potential Agents in Prevention and Therapy of Prostate Diseases

Abstract: In recent years, the progress of science and medicine greatly has influenced human life span and health. However, lifestyle habits, like physical activity, smoking cessation, moderate alcohol consumption, diet, and maintaining a normal body weight represent measures that greatly reduce the risk of various diseases. The type of diet is very important for disease development. Numerous epidemiological clinical data confirm that longevity is linked to predominantly plant-based diets and it is related to a long lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 217 publications
(226 reference statements)
0
21
0
1
Order By: Relevance
“…Literature data indicate that plant polyphenols are effective in preventing and inhibiting the growth of gastrointestinal neoplasms, where they are found in the highest amounts after consumption. They are also effective in the case of colorectal neoplasms [ 51 ] and contribute to the inhibition of the development of many other neoplasms, e.g., melanoma, prostate and hormone-dependent tumors [ 54 , 90 ]. Furthermore, research indicates that polyphenols, such as apigenin, quercetin, resveratrol or gallic acid, have anti-angiogenetic properties [ 91 ].…”
Section: Classes Of Phenolic Compounds and Their Biological Role Fmentioning
confidence: 99%
“…Literature data indicate that plant polyphenols are effective in preventing and inhibiting the growth of gastrointestinal neoplasms, where they are found in the highest amounts after consumption. They are also effective in the case of colorectal neoplasms [ 51 ] and contribute to the inhibition of the development of many other neoplasms, e.g., melanoma, prostate and hormone-dependent tumors [ 54 , 90 ]. Furthermore, research indicates that polyphenols, such as apigenin, quercetin, resveratrol or gallic acid, have anti-angiogenetic properties [ 91 ].…”
Section: Classes Of Phenolic Compounds and Their Biological Role Fmentioning
confidence: 99%
“…On the other hand, the intake of long-chain omega-3 polyunsaturated fatty acids does not seem to be associated with lower cancer incidence (26). Vitamin D could also play an important role, as both low and high concentrations are associated with an increased risk (29).…”
Section: Prostate Cancermentioning
confidence: 99%
“…Regarding the relationship between isoflavones and prostate diseases, research has reported that isoflavones exert a preventive effect on prostate carcinogenesis due to their phytoestrogen action [ 16 ]. In addition, many investigators have paid special attention to the anti-cancer effects of isoflavones in prostate cancer [ 67 , 68 , 69 ]. In contrast to prostate cancer, studies on the pharmacological effects of isoflavones on BPH are smaller.…”
Section: Management Of Benign Prostate Hyperplasia With Polyphenolmentioning
confidence: 99%
“…Interestingly, this study also showed that there were no significant differences in plasma levels of luteinizing hormone (LH) or the estradiol and testicular levels of testicular steroidogenic acute regulatory peptide between the phytoestrogen-rich included isoflavones and the phytoestrogen-free Regarding the relationship between isoflavones and prostate diseases, research has reported that isoflavones exert a preventive effect on prostate carcinogenesis due to their phytoestrogen action [16]. In addition, many investigators have paid special attention to the anti-cancer effects of isoflavones in prostate cancer [67][68][69]. In contrast to prostate cancer, studies on the pharmacological effects of isoflavones on BPH are smaller.…”
Section: Isoflavonesmentioning
confidence: 99%